Pengaruh Problem Based Writing with Peer Review (PW-PR) terhadap Kemampuan Berpikir Kritis Siswa pada Konsep Pencemaran Lingkungan - Zulhia Usna Prihatin; I Wayan Karmana; Titi Laily Hajiriah (Department of Biology Education, FSTT, Mandalika University of Education, Indonesia., 2021)
The purpose of this study was to determine how the effect of Problem Based Writing with Peer Review (PW-PR) on students' critical thinking skills. This type of research is quasi-experimental. The population in this study were students of class X SMAN 1 Praya Timur, Central Lombok Regency, with a total of 24 students. Sampling was done by purposive sampling, ie classes were taken based on a specific purpose. The data analysis technique used is the N-Gain index formula. Based on the results of the pretest and posttest data analysis showed that, there was a significant increase from the N-Gain index of 0.36 to the N-Gain index of 0.44. The standard N-Gain index is 0.7 smaller than the research N-Gain index (0.7 < 0.44). Because the N-Gain index of the research results is smaller than the standard N-Gain index and the results are positive so that it is categorized as moderate, it can be concluded that there is an effect of Problem Based Writing with Peer Review (PW-PR) on students' critical thinking skills.